The Legal Policy of the Minimum Wage for Workers' Adequate Subsistence - Anis Rukmawati (Faculty of Law, Universitas Sebelas Maret, 2021)
This legal study seeks to determine wage policies through minimum wages in Government Regulation 36 of 2021 concerning Wages in order to provide workers with a decent standard of living and to identify legal certainty guarantees. This is a prescriptive type of normative legal research employing a statute-based methodology. Utilized types of legal materials include primary and secondary legal materials. The technique used to collect legal materials is called